Influence Of Organizational Culture And Work Stress On Employee Satisfaction - Fadly Halim Saragih; Muhammad Andi Prayogi (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to determine and partially analyze the influence of organizational culture on employee job satisfaction at PT. Garuda Indonesia (Persero) Tbk Medan branch, to partially determine the effect of work stress on employee job satisfaction at PT. Garuda Indonesia (Persero) Tbk Medan branch and to find out and analyze simultaneously the influence of organizational culture and work stress on employee job satisfaction at PT. Garuda Indonesia (Persero) Tbk. Garuda Indonesia (Persero) Tbk Medan branch. The population in this study was all employees of PT. Garuda Indonesia (Persero) Tbk Medan branch which has a total of 35 people, where the sempel collection uses the entire population because of the relatively small population of 35 respondents. The data collection techniques used in this study were questionnaires and interviews. The analytical techniques used in this study are classical assumptions, multiple regression, hypothesy tests, and coefficients of determination. Based on the results of the Organizational Culture research, it has a partial significant and positive effect on employee job satisfaction at PT. Garuda Indonesia (Persero) Tbk Medan branch. Work stress partially has a significant and positive effect on the job satisfaction of PT. Garuda Indonesia (Persero) Tbk Medan branch. Organizational culture and work stress simultaneously affect the job satisfaction of PT. Garuda Indonesia (Persero) Tbk Medan branch.